Temporal transcriptional control of neural induction in human induced pluripotent stem cells - Gupta, Shakti; Polit, Lucia Dutan; Fitzgerald, Michael; Rowland, Helen A.; Murali, Divya; Buckley, Noel J.; Subramaniam, Shankar (Frontiers in Molecular Neuroscience, 2023)
Introduction Neural induction of human induced pluripotent stem cells represents a critical switch in cell state during which pluripotency is lost and commitment to a neural lineage is initiated. Although many of the key transcription factors involved in neural induction are known, we know little of the temporal and causal relationships that are required for this state transition. Methods Here, we have carried out a longitudinal analysis of the transcriptome of human iPSCs undergoing neural induction. Using the temporal relationships between the changing profile of key transcription factors and subsequent changes in their target gene expression profiles, we have identified distinct functional modules operative throughout neural induction. Results In addition to modules that govern loss of pluripotency and gain of neural ectoderm identity, we discover other modules governing cell cycle and metabolism. Strikingly, some of these functional modules are retained throughout neural induction, even though the gene membership of the module changes. Systems analysis identifies other modules associated with cell fate commitment, genome integrity, stress response and lineage specification. We then focussed on OTX2, one of the most precociously activated transcription factors during neural induction. Our temporal analysis of OTX2 target gene expression identified several OTX2 regulated gene modules representing protein remodelling, RNA splicing and RNA processing. Further CRISPRi inhibition of OTX2 prior to neural induction promotes an accelerated loss of pluripotency and a precocious and aberrant neural induction disrupting some of the previously identified modules. Discussion We infer that OTX2 has a diverse role during neural induction and regulates many of the biological processes that are required for loss of pluripotency and gain of neural identity. This dynamical analysis of transcriptional changes provides a unique perspective of the widespread remodelling of the cell machinery that occurs during neural induction of human iPSCs.